The Development of Transformative Agency of Teachers in Teaching Research Activities in China - Diao, Chunting; Zhou, Xuan; Mao, Qiming; Hong, Jianzhong (Frontiers in Psychology, 2022)
Teaching research activities in China are teachers' practical and reflective research on teaching. These required activities are meant to ensure quality education and facilitate teachers' professional development. However, in teaching research activities, teachers encounter many challenges such as low efficiency and weak team collaboration. These problems make it hard to achieve the expected outcomes. W Primary School reformed its activities using Change Laboratory, a formative intervention approach to workplace learning and development based on activity theory. The data collected included 7 recorded meetings in the Change Laboratory. The conversations in the meetings were then transcribed into texts. A deductive method of content analysis was used to code the data with a focus on categorizing teachers' comments about transformative agency. The findings showed: 1) There were five types of transformative agency: resisting, criticizing, explicating, envisioning and committing to actions. Resisting and criticizing were represented less frequently, and taking action did not emerge as a type of transformative agency. 2) The comments about transformative agency in relation to tools were more frequent than comments about other elements in the activity system. 3) There were some differences in the expression of transformative agency across participants. At the end of the paper, the implications for the development of Teaching Research Activities are discussed.